2019
DOI: 10.1002/ps.5516
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the potassium ion channel genes SK and SH as a novel approach for control of insect pests: efficacy and biosafety

Abstract: BACKGROUND Potassium ion channels play a critical role in the generation of electrical signals and thus provide potential targets for control of insect pests by RNA interference. RESULTS Genes encoding the small conductance calcium‐activated potassium channel (SK) and the voltage‐gated potassium channel (SH) were knocked down in Tribolium castaneum by injection and oral delivery of dsRNA (dsTcSK and dsTcSH, respectively). Irrespective of the delivery mechanism a dose‐dependent effect was observed for knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…The selection of suitable species-specific target genes is an important initial step in developing effective RNAi-based control strategies. 38 In this study, we selected 23 candidate genes previously reported as effective RNAi targets in T. castaneum, 32,33 Spodoptera exigua, 34 Diaphorina citri 35 and Heortia vitessoides. 36 Surprisingly, of the 23 genes whose knockdown caused significant mortality in other insects, 70% of candidates caused less than 15% mortality, and only three induced more than 50% mortality in H. cunea larvae in the initial screening (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection of suitable species-specific target genes is an important initial step in developing effective RNAi-based control strategies. 38 In this study, we selected 23 candidate genes previously reported as effective RNAi targets in T. castaneum, 32,33 Spodoptera exigua, 34 Diaphorina citri 35 and Heortia vitessoides. 36 Surprisingly, of the 23 genes whose knockdown caused significant mortality in other insects, 70% of candidates caused less than 15% mortality, and only three induced more than 50% mortality in H. cunea larvae in the initial screening (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 23 genes were selected as candidate targets from Coleoptera, Lepidoptera, and Hemiptera insects (Table 1): 19 of which were previously reported for top mortality in T. castaneum 32,33 and 4 were reported for effective control in other insects such as Spodoptera exigua, 34 Diaphorina citri, 35 and Heortia vitessoides. 36 H. cunea homologous genes were detected in the H. cunea transcriptome database using the local BLAST program.…”
Section: Selection Of Target Genes and Synthesis Of Dsrnamentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared with the extensive and long-term studies on sodium channels, only a few entomological studies have focused on Kv channels and regarded them as molecular targets for insecticide development. 6,16,32 In this study, we concentrated on Shab (Kv2) channel and cloned the Shab gene from P. xylostella for the first time. Consistent with the D. melanogaster and A. aegypti, 33 there is only one Shab gene (LOC105386449) in the P. xylostella genome.…”
Section: Discussionmentioning
confidence: 99%
“…We also injected dsGFP into cockroaches and found no effect on aaNAT transcription (results not shown). However, in view of recently reported off-target effects of dsGFP injection (impairing its host's core biological functions via affecting several genes implicated in central metabolic and developmental processes associated with RNA processing and transport, hormone metabolism, immunity and response to external stimulus and to stress) to control for nonspecific side effects of RNAi [33,34], we favored water as a control for RNAi, alone, as a widely used accepted approach in RNAi studies in insects [35,36].…”
Section: Preparation and Injection Of Dsrnamentioning
confidence: 99%